Trends in human papillomavirus (HPV) vaccination initiation among adolescents aged 13-17 by metropolitan statistical area (MSA) status, National Immunization Survey - Teen, 2013 - 2017 - Tanja Y. Walker; Laurie D. Elam-Evans; Charnetta L. Williams; Benjamin Fredua; David Yankey; Lauri E. Markowitz; Shannon Stokley (Taylor & Francis Group, 2020)
Disparities in HPV vaccination coverage by metropolitan statistical area (MSA) status were observed in the 2016 and 2017 National Immunization Survey - Teen (NIS-Teen). In 2017, HPV vaccination initiation (≥1dose) coverage was 11 percentage points lower for adolescents living in non-MSAs (mostly rural areas) and 7 percentage points lower among those living in MSA, non-principal cities (suburban areas) compared to those living in MSA, principal cities (mostly urban areas). In order to understand how this disparity has changed over time, we examined trends in HPV vaccine initiation by MSA status from 2013 to 2017. Weighted linear regression by survey year was used to estimate annual percentage point changes in HPV vaccination initiation. The five-year average annual percentage point increases in HPV vaccination initiation coverage were 5.2 in mostly urban areas, 4.9 for suburban areas, and 5.2 for mostly rural areas. Despite increases in each MSA area, coverage in mostly rural areas was consistently and significantly lower than coverage in mostly urban areas. Coverage was significantly lower among teens living in mostly rural areas regardless of poverty status, sex, and race/ethnicity except among black, non-Hispanic adolescents. There was no significant change in the magnitude of the disparity between mostly urban areas and mostly rural areas over time (p = .98). A better understanding of the facilitators and barriers to HPV vaccination in mostly rural areas is needed to identify and implement targeted strategies to improve HPV vaccination coverage and reduce these disparities.